Attenuation and modification of the ballast water microbial community during voyages into the Canadian Arctic. Issue 5 (May 2017) - Johansson, Mattias L.; Chaganti, Subba Rao; Simard, Nathalie; Howland, Kimberly; Winkler, Gesche; Rochon, André; Laget, Frederic; Tremblay, Pascal; Heath, Daniel D.; MacIsaac, Hugh J.
Abstract: Aim: Ballast water is a major vector of non‐indigenous species introductions world‐wide. Our understanding of population dynamics of organisms entrained in ballast is largely limited to studies of zooplankton and phytoplankton. Bacteria are more numerous and diverse than zooplankton or phytoplankton, yet remain comparatively understudied. We apply a metagenomics approach to characterize changes in the microbial ballast water community over the course of three voyages on one ship, and assess the effects of ballast water exchange (BWE), spring/summer sampling month and time since voyage start. Location: Quebec City and Deception Bay, Quebec, and the coastal marine region offshore of eastern Canada. Methods: We used universal primers to Ion Torrent sequence a fragment of the bacterial 16S ribosomal DNA for samples collected over three voyages of one ship between Quebec City and Deception Bay in June, July and August 2015. We compared richness (total number of species in the community) and diversity (accounts for both species abundance and evenness) using linear mixed‐effects analysis and compared community composition using non‐metric multidimensional scaling and permutational multivariate analysis of variance. Initial comparisons were between months. Subsequent analyses focused on each month separately. Results: Ion Torrent sequencing returned c . 2.9 million reads and revealed monthly differences in diversity and richness, and in community structure in ballast water. June had higher richness and diversity than either July or August, and showed most clearly the effect of BWE on the microbial community. Main conclusions: Our results suggest that environmental conditions associated with different spring/summer sampling months drive differences in microbial diversity in ballast water. This study showed that BWE removes some components of the freshwater starting microbial community and replaces them with other taxa. BWE also changed proportional representation of some microbes without removing them completely. It appears that some taxa are resident in ballast tanks and are not removed by BWE.